The impact of social network use on adolescent depression: the chain mediation between self-objectification and body satisfaction - Tang, Yiming; Xu, Min; Tan, Zhongwei; Liu, Yong (Frontiers in Psychology, 2024)
Introduction: Adolescents are in the transitional stage from childhood to adulthood, a critical period for individual physical and mental development. With the rapid development of the Internet, social networking has become an integral part of adolescents' daily lives. However, the information that adolescents are exposed to on social networks is often processed and embellished, which may cause them to become physically dissatisfied and lead to emotional problems, such as depression. We investigated the chain-mediating effects of self-objectification and body satisfaction on the relationship between social network use and depression.Methods: We utilized questionnaire data of 2025 adolescents from two secondary schools and one high school in China.Results: Our results demonstrated that (1) there are obvious sex differences in the intensity of social network use and active and passive social network use among adolescents, with usage higher among girls than for boys; (2) self-objectification and body satisfaction play a mediating role in the relationship between the intensity of social network use and adolescent depression, as well as the presence of chain-mediating roles;